Does p-coumaric acid improve cardiac injury following LPS-induced lung inflammation through miRNA-146a activity? - Kheiry, Maryam (Avicenna J Phytomed, 2020)
OBJECTIVE: In cardiovascular diseases, inflammatory response plays an important role and affects heart function. As a flavonoid compound, p-coumaric acid (pCA), commonly exists in many fruits and vegetables and has a therapeutic effect on inflammatory diseases due to its anti-inflammatory properties. The purpose of the present study was to investigate pCA anti-inflammatory effect and the miRNAs (miRs) signaling pathway involved in cardiac inflammation following lipopolysaccharide-induced acute lung injury (ALI). MATERIALS AND METHODS: Thirty-two Sprague-Dawley male rats were divided into 4 groups: control (received saline for 10 days, i.p.), LPS (received saline for 10 days+5 mg/kg LPS on day 8, intratracheally), pCA (received pCA 100 mg/kg for 10 days, ip), and LPS+pCA (received LPS+pCA). The level of IL-1β, IL-18 in heart tissue and IL-1β in bronchoalveolar lavage fluid (BALF) was determined by ELISA kits. Also the level of lactate dehydrogenase (LDH) in heart tissue and myeloperoxidase (MPO) in lung tissue were measured, and pCA effect on miR- 146a in heart tissue was analyzed. RESULTS: Data showed that 100 mg/kg of pCA significantly suppressed LDH activity (p<0.05), IL-18 (p<0.05) and IL-1β (p<0.01) level in heart tissue. Also, in BAL, IL-1β and MPO levels were significantly reduced (p<0.001). Finally, pCA modulated activation of miR-146a (p<0.05) in LPS -induced cardiac injury. CONCLUSION: These findings indicated that LPS causes cardiac dysfunction and pre-treatment with pCA, as an anti-inflammatory agent, improved cardiac inflammation through modulation of miR-146a, and reducing cytokines and LDH activity.